The Role of Pentahelix's Effective Collaboration in Developing the Frugal Innovation Strategy for the â€œPekarangan Pangan Lestari (P2L)â€ Program - Khouroh, Umu; Ratnaningsih, Christina Sri; Rahayudi, Bayu (Proceedings of International Conference of Graduate School on Sustainability, 2022)
The purpose of this study is to examine the role of pentahelix in the relationship between frugal innovation strategies and the business performance of the Pekarangan Pangan Lestari (P2L) program actors. This research design uses explanatory research with a quantitative approach. Data were obtained from the actors of the P2L program in Malang Regency. This study uses an online survey by sending a questionnaire to a group of the P2L program. The data collected and can be analyzed is 62 data. Data analysis in this study used descriptive analysis and SEM-PLS. The results show that pentahelix collaboration becomes a moderator in improving and strengthening frugal innovation strategies to produce the optimal performance of P2L program group members. Through several stages of frugal innovation which include empathizing, defining, ideating, bricolage, prototype, and testing combined with pentahelix collaboration, it is hoped that the managers/members of the P2L program group can improve their performance. This study provides empirical evidence of the use of the frugal innovation strategy and pentahelix collaboration implemented in the P2L program in solving problems of economic dynamics, providing employment opportunities due to COVID'19 as well as meeting nutritional needs to overcome stunting and overcome food insecure villages. Keywords: Frugal Innovation, Pentahelix Collaboration, Performance, â€œPekarangan Pangan Lestariâ€ (P2L) program